Use Arduino as a modbus slave over RTU - Simões, José (2016)
The purpose of this article is to accomplish various appointed objectives. The objectives of this article include: to become acquainted with the Modbus RTU protocol, to implement the Modbus RTU protocol onto an Arduino Uno microcontroller as a slave and to test the Arduino Uno slave using a free Modbus master program. The Arduino Uno slave must be fully configurable where the user can set all the Modbus communication parameters such as slave ID, parity, communication rate, number of stop bits, etc. The user must also be able to assign values or variables to a particular coil or register regardless of the order of the previously used coils or registers. The Arduino slave must also communicate with the master over a RS232 connection.